Thoughts on files. (November 2021) - Clapton, Gary
With the benefit of an anthropological attention to the importance of 'things' and the relations between ourselves and things ('artefacts'), this paper gives attention to the Social Work File. Despite the rise of electronic recording, social work archives remain full of thousands of files that are increasingly accessed, especially by those who have been in care, and physical file-keeping remains a regular feature of practice. There is already a body of literature relating to the information in social work files, however this paper shifts the focus from this to the nature and role of the File itself. 'Hidden in plain sight' but laden with meaning and capacity, I identify the little we know already about the file. The various ways files and their authors and subjects, can interact are explored together with the file's symbolic properties and the power held by the file's owner, and the ability of the file to 'other' its subject. Whilst we understand that the practice shapes the file, how might the file shape practice?